Linking food and nutrition security: past lessons and future opportunities - Bouis, Howarth E.; Hunt, Joseph (World Scientific Publishing, 1999)
Traditional food security strategies are reviewed and generally found to have a weak impact on lowering child malnutrition. Unless these programs are properly targeted and linked to employment and micro-credit opportunities for women, they are unlikely to be effective or sustainable. The links between food policy and nutrition security require greater attention to dietary quality through agricultural research and technology, directed to reducing both undernutrition and overnutrition; social security polices that protect poor women and children; and food aid polices that are developmental in intent and impact.One element in the final solution to malnutrition is to provide increased consumption of a range of non staple foods. To reach the poor, this will require a relatively large investment in agricultural research and other public and on-farm infrastructure over several decades. In the medium run, a much smaller investment in improving the nutrient content of food staples through plant breeding can make a major contribution to reducing deficiencies in selected micronutrients. The role of women is central to nutrition outcomes through child care, so that policies and programs must consider how to enhance women's decision-making power in the household, how they affect time demands on women, and how to increase women's education and nutritional knowledge. Finally, community-based programs, which are central to the RETA strategy for improved nutrition, should be used to monitor the nutrition effects of agricultural policies and programs and to provide feedback to agricultural policymakers as to how to enhance the positive effects and minimize the negative effects of agricultural policies and programs.